Analisis Self-Esteem Anak Berkebutuhan Khusus di SMA Negeri 3 Padang serta Implikasinya dalam Bimbingan dan Konseling - Ngadiman, Dyah Ayu Sakinah; Yendi, Frischa Meivilona; Nurfarhanah, Nurfarhanah; Putriani, Lisa (Current Issues in Counseling, 2023)
Children with special needs are children who need the same education and services as other children, so that they can realize that every human being must have advantages. One of the problems of children with special needs is their low self-esteem. Therefore, the problem to be studied in this research is, "Analysis self-esteem of children with special needs in Padang and its implications in guidance counseling". This type of research is qualitative research with a phenomenological approach. The subjects in this study were 4 children with special needs and 8 informants. The research instruments used in this study were interview guidelines, observation and documentation. The results showed that, self-esteem of children with special needs in the aspect of self-liking was in the low category and the self-esteem in the self-competence aspect is in the medium category. The concluded is every child with special needs has a different self-esteem.